2017
DOI: 10.15191/nwajom.2017.0505
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Inland Extent of Lake Effect Snow Bands Downwind of Lake Ontario

Abstract: Determining the inland extent (IE) of lake effect snow (LES) is an ongoing operational forecasting challenge at the Albany and Binghamton National Weather Service (NWS) forecast offices, and several other NWS forecast offices in the Great Lakes region. Assuming favorable conditions for development of LES, determining how far inland snow bands will extend is critical to forecasters making decisions supporting the NWS watch/ warning/advisory program and resulting impact-based decision support services. This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 26 publications
(31 reference statements)
3
23
0
Order By: Relevance
“…We used archived NEXRAD images and other meteorological data to begin to assess the frequency of LE snowstorms that travel inland into the Catskills, and to confirm the importance of LE snow for the Catskill/Delaware Watershed that is important for the NYCWSS. Lake-effect storms can extend quite far inland and can contribute a significant percentage of the total snowfall to inland sites (e.g., Schmidlin, 1992;Villani, Jurewicz & Reinhold, 2017). Yet there has been very little discussion in the literature about the significance of the contribution of LE snow to the Catskills because the Catskill/Delaware Watershed in the Catskills is so far inland from the Great Lakes (~170 km from the closest point on the shoreline of Lake Ontario to the Cannonsville Reservoir in the Cannonsville Basin, and ~300 km from the closest point on the shoreline of Lake Erie to the Cannonsville Basin) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used archived NEXRAD images and other meteorological data to begin to assess the frequency of LE snowstorms that travel inland into the Catskills, and to confirm the importance of LE snow for the Catskill/Delaware Watershed that is important for the NYCWSS. Lake-effect storms can extend quite far inland and can contribute a significant percentage of the total snowfall to inland sites (e.g., Schmidlin, 1992;Villani, Jurewicz & Reinhold, 2017). Yet there has been very little discussion in the literature about the significance of the contribution of LE snow to the Catskills because the Catskill/Delaware Watershed in the Catskills is so far inland from the Great Lakes (~170 km from the closest point on the shoreline of Lake Ontario to the Cannonsville Reservoir in the Cannonsville Basin, and ~300 km from the closest point on the shoreline of Lake Erie to the Cannonsville Basin) (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ice coverage and air-water temperature contrast, fetch, wind direction, and wind speed also affect the development and intensity of LE snow (e.g., see Villani, Jurewicz & Reinhold, 2017). Long fetch can increase the intensity of the LE storms by providing a greater surface area to allow more evaporation from the non-ice-covered lake surface (Steiger et al, 2013).…”
Section: Background Lake Effect Snowfall In the Eastern Great Lakes Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on four variables that influence the inland and orographic enhancement of sea-effect precipitation: 1) the mean boundary layer wind direction, 2) the mean boundary layer wind speed U, 3)Ĥ, and 4) SiCAPE. The mean direction and speed of the boundary layer flow influence the location, intensity, and inland penetration of lake-effect precipitation (e.g., Alcott and Steenburgh 2013;Villani et al 2017;V18). They are also integral to orographic precipitation processes, with stronger crossbarrier flow associated with a greater upslope moisture flux and decreased blocking (e.g., Sinclair et al 1997;Neiman et al 2002;Colle 2004;Panziera and Germann 2010;Yuter et al 2011).Ĥ provides a precise quantification of the terrain-induced flow behavior, accounting for barrier height, the barrier-normal flow component, and the static stability of the impinging air mass.…”
Section: B Environmental Conditionsmentioning
confidence: 99%
“…In addition, the atmospheric conditions and air-surface interactions must be considered over a larger area. For example, Villani et al (2017) found that an L2L connection, or a multilake connection as they called it, provided a greater tendency for LES snowbands over the downstream lake to extend inland for greater distances. In addition, Rose (2000) investigated an L2L event from Lake Michigan to Lake Erie using mesoscale model simulations and found that eliminating the presence of Lake Michigan 1) reduced the snowfall maximum by two-thirds, 2) reduced vertical ascent by one-half, and 3) decreased cloud depth by several hundred meters.…”
Section: Introductionmentioning
confidence: 99%